2015
DOI: 10.1590/0103-8478cr20131546
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação física e química e aceitação pelo consumidor de laranjas 'Valência', produzidas sob sistemas de cultivo orgânico e convencional

Abstract: RESUMO O objetivo foi verificar a influência do sistema de cultivo, orgânico e convencional, sobre as características físicas e químicas e sobre a aceitação pelo consumidor de laranjas 'Valência' (Citrus sinensis (L.) Osb.). Os pomares foram instalados

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…Based on the physicochemical characteristics described by Schwarz et al (2018) for 'Okitsu' tangerines, it was found that the treatments did not affect these parameters in this work. Regarding oranges, it was observed that parameters such as diameter, SS, and TA were similar to those recorded by Petry et al (2015) and the average mass followed the values described for the cultivar Valencia (Schwarz et al, 2018), so, with no effect of the treatments. Moreover, the PCI, whose minimum export value must be 2 to oranges (Spósito et al, 2006), has always remained above 4 in all treatments.…”
Section: Discussionsupporting
confidence: 69%
“…Based on the physicochemical characteristics described by Schwarz et al (2018) for 'Okitsu' tangerines, it was found that the treatments did not affect these parameters in this work. Regarding oranges, it was observed that parameters such as diameter, SS, and TA were similar to those recorded by Petry et al (2015) and the average mass followed the values described for the cultivar Valencia (Schwarz et al, 2018), so, with no effect of the treatments. Moreover, the PCI, whose minimum export value must be 2 to oranges (Spósito et al, 2006), has always remained above 4 in all treatments.…”
Section: Discussionsupporting
confidence: 69%
“…Under FO, soil management depends on the fruit crop, and as these are perennial crops, generally with a deep root system, soil preparation is intense when planting the crop, both on the surface and at depth. However, after planting the crop, soil management is generally less intensive, with the soil only being turned between crop rows to control weeds, or around the plants for fertilizer (PETRY et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nos PFs o manejo do solo é dependente da cultura frutífera, e considerando que se tratam de culturas perenes, em geral com sistema radicular profundo, para a implantação da cultura, o preparo do solo é intenso, tanto superficialmente como em profundidade. Porém, geralmente, após a implantação da cultura, o manejo do solo é menos intensivo, sendo apenas realizadas operações de revolvimento nas entrelinhas da cultura para o controle de plantas daninhas ou no entorno das plantas para a adubação (PETRY et al, 2015).…”
Section: Introductionunclassified